2022
DOI: 10.1115/1.4049757
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Radon Excess Lung Cancer at the Babylon Cement Plant in Iraq

Abstract: In the present work, Radon Excess Lung Cancer (ELC) is estimated for fourteen soil samples from Babylon cement plant in Iraq. CR-39 nuclear track detector is utilized to measure the uranium content and radon 222Rn concentrations in soil samples. Uranium concentrations in soil samples varied from 0.008 to 0.05 ppm with mean value 0.025±0.013. Radon concentrations is founded between 31 and 92 Bq/m3 with mean value 56.72 and standard division, SD, 17.29. Radon Excess Lung Cancer per Million Persons per Year is de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…It was within the internationally permitted levels. [15] Israa Kamil Ahmed also studied 14 samples of cement spread in the markets of Babylon using passive technic CR-39 track detector to calculate uranium and radon concentration its effect on humans because it may cause lung cancer, as the average value for uranium concentration was 0.025 ppm , the main value for radon concentration was 56.72 Bq.m -3 , which is within the internationally permitted levels [16] Different samples of soil, rocks and water were taken from different locations in the Al-Amiriyah area in Baghdad to determine the concentration of radon gas in these samples to find out the amount of danger that threatens the residents of this area using a nuclear track detector CR-39. The rate of radon concentration was between 47.3 -54.2 Bq.m -3 , within the internationally permitted levels.…”
Section: Introductionmentioning
confidence: 93%
“…It was within the internationally permitted levels. [15] Israa Kamil Ahmed also studied 14 samples of cement spread in the markets of Babylon using passive technic CR-39 track detector to calculate uranium and radon concentration its effect on humans because it may cause lung cancer, as the average value for uranium concentration was 0.025 ppm , the main value for radon concentration was 56.72 Bq.m -3 , which is within the internationally permitted levels [16] Different samples of soil, rocks and water were taken from different locations in the Al-Amiriyah area in Baghdad to determine the concentration of radon gas in these samples to find out the amount of danger that threatens the residents of this area using a nuclear track detector CR-39. The rate of radon concentration was between 47.3 -54.2 Bq.m -3 , within the internationally permitted levels.…”
Section: Introductionmentioning
confidence: 93%
“…Recent studies have indicated that the annual effective dose from 222 Rn is 1.3 mSv y − 1 due to the total natural exposure of 2.4 mSv y − 1 to dedicate (more than 50%) [20][21][22][23][24]. The World Health Organization (WHO) estimated that from all lung cancer deaths there is 1-7% due to the level of radon in water compared to 10-15% of total indoor radon may be attributed directly to out gassing from tap water [16,25].…”
Section: Introductionmentioning
confidence: 99%